Participação do circuito dopaminérgico nas alterações do comportamento de medo inato de camundongos infectados pelo Toxoplasma gondii - Meurer, Ywlliane da Silva Rodrigues (2012)
The protozoan parasite Toxoplasma gondii transforms the innate aversion of rats for cat urine into a fatal attraction, that increases the likelihood of the parasite completing its life cycle in the cat s intestine. The neural circuits implicated in innate fear, anxiety, and learned fear all overlap considerably, raising the possibility, that T. gondii may disrupt all of these nonspecifically. In this study, we evaluated immunoreactivity for tyrosine hydroxylase (TH) in areas associated with innate fear of infected male swiss mice. The latent Toxoplasma infection converted the aversion of mice to feline odors into attraction. This loss of fear is remarkably specific, as demonstrated by Vyas et al (2007), because infection did not diminish learned fear, anxiety-like behavior, olfaction, or nonaversive learning. However, the neurochemical mechanism related to alterations in innate fear due to T. gondii infection remains poorly studied. 20 mice were inoculated with bradyzoites (25 cysts) from a Toxoplasma gondii (Me-49 strain). The brains were removed after 60 days, sectioned and processed for TH immunohistochemistry. The correlation between the amount of cysts per area and the densitometric analysis of neurotransmitter reactivity was low in the areas implicated in innate fear of infected animals, when comparated with noninfected controls